The Partiality of Family Law Reform towards Women: A Comparative Study of Women's Material Rights after Divorce in Muslim Countries - Falah, Bahrul; Lukita, Jimmy; Sibawaihi, Muhammad; Ikhwan, Muhammad; Rohmatuszahroh, Anita Intan (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2023)
This research examines post-divorce maintenance partiality in Indonesia, South Yemen, and Turkey. After that, the partiality will be correlated with legal reform from several aspects, including its historicity and political turmoil. The type of research used is normative research with a comparative approach. Primary data is obtained from legal materials regarding post-divorce maintenance in the three countries that are the object of study. The results showed that post-divorce maintenance in Turkey and South Yemen did not provide much material benefit to the ex-wife, in contrast to the condition of post-divorce maintenance in Indonesia. This is influenced by the description of the pattern of husband and wife relations in Turkish and South Yemeni law which was influenced by the secularism and feminism movements, while Indonesia did not experience these movements. This research implies that there are historical factors of legal reform and the influence of political turmoil on material partiality towards women. Penelitian ini mengkaji keberpihakan nafkah pasca perceraian di Indonesia, Yaman Selatan, dan Turki. Setelah itu, keberpihakan tersebut akan dikorelasikan dengan reformasi hukum dari beberapa aspek, termasuk historisitas dan gejolak politiknya. Jenis penelitian yang digunakan adalah penelitian normatif dengan pendekatan komparatif. Data primer diperoleh dari bahan-bahan hukum mengenai nafkah pasca perceraian di tiga negara yang menjadi objek penelitian. Hasil penelitian menunjukkan bahwa nafkah pasca perceraian di Turki dan Yaman Selatan tidak memberikan keuntungan yang banyak secara materiil kepada mantan istri. Berbeda dengan kondisi nafkah pasca perceraian di Indonesia. Hal ini dipengaruhi oleh gambaran pola relasi suami istri dalam hukum Turki dan Yaman Selatan yang dipengaruhi oleh gerakan sekularisme dan feminisme, sedangkan Indonesia tidak mengalami gerakan tersebut. Penelitian ini mengimplikasikan adanya faktor sejarah reformasi hukum dan pengaruh gejolak politik terhadap keberpihakan materiil terhadap perempuan.